(untitled) (The Strategic Review for Southern Africa, 2022)
The European Union and its member states have developed a set of strategies for the Indo-Pacific region. Recognising that regions are constantly subject to reinterpretation, negotiation and contestation, this paper analyses the EU’s framing of the Indo-Pacific as an exercise of territorial delineation, justifications for interference, projected regional attributes and relations with actors in the region. Particular attention is dedicated to the role attributed to the African countries constituting the Western shore of the Indo-Pacific. The paper examines the four Indo-Pacific strategies that have emerged since 2018 within the EU, namely the strategies launched by France, Germany, the Netherlands, and the European Union. It highlights and compares the differences and similarities between them and argues that although the four strategies agree on many priorities, especially on commercial interests, there are notable differences in terms of projected military involvement and the framing of China. Considerable divergences unfold with respect to Africa, both regarding its belonging to the Indo-Pacific and the role it is expected to play. Only the EU and French documents develop a strategic approach towards Africa, notably through regional organisations. Yet, they concede little agency to the African actors. Given the fragmented and unilateral approach of the four strategies, the scope for Euro-African collaboration in the Indo-Pacific remains uncertain.